LITERARY ANALYSIS OF ZAMYATIN’S “WE” AND OLJAS SULEIMENOV’S “AZ I YA”: A COMPARATIVE STUDY (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
This article examines Evgeny Zamyatin’s “We” and Oljas Suleimenov’s “Az i Ya” through a comparative literary perspective. Both works emerge from different time periods and genres, yet they share a common function: resistance against ideological suppression. The study analyzes how symbolism, characterization and setting reveal deeper themes of individuality versus collectivism, and cultural memory versus political censorship. Findings demonstrate that Zamyatin critiques totalitarian control through dystopian fiction, while Suleimenov reclaims Turkic cultural identity through literary philology. Both authors ultimately argue that true human development depends on freedom — whether personal or cultural.